A Comparative Study on Different Feeding Machines to Growth, Water Quality and Economic Performance in Nile Tilapia (Oreochromis niloticus) Commercial Farming - Songphatkaew, Jaruwan; Yakupitiyage, Amararatne; Ganmanee*, Monthon; Tsutsui, Isao (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Acomparative study of two different feeding methods; fixed station feeder (AF) and mobile blower feeder (BF), on growth, water quality and economical performance in Nile Tilapia (Oreochromis niloticus) were done in earthen pond commercial farm in Petchaburi province, central Thailand. Monosex tilapias (average initial body weight of 300 g) were stocked in six 8000-11200 m2 earthen ponds at a density of ca. 1 fish/ m2 and cultured for 120 days. Fish were fed with a MN 11 commercial tilapia pellet feed (30% protein). Results showed survival, yield, body composition and feed utilization in fish fed using (AF) and (BF) were not statistically difference (P>0.05). However, growth performance was higher in fish fed using blower feeder. Distribution of fish in earthen pond during feeding time between 2 feeder machines was different. Most fish in pond fed using (AF) method aggregated near the outlet (feeding area), while the uniform distribution was observed in pond fed by (BF) method. There were no significant differences in almost all water quality parameters and perform at the optimal level. In addition, there was no significant difference in the economic performance between two feeding methods. Therefore, the (AF) might be the considerable options of feeding machine which can improve growth performance for Nile tilapia commercial farming. Keywords: Fixed Station Feeder, Mobile Blower Feeder, Nile Tilapia, Growth, Commercial Farming *Corresponding author: E-mail: kkmontho@gmail.com